Brief Notes: Kinematically Admissible Solutions for the Incipient Stage of Earth Moving Processes in the Cases of Various Pushing Wall Forms - Trąmpczyński, W; Szyba, D. (Engineering Transactions, 1991)
Kinematically admissible solutions for earth-moving processes due to various pushing wall forms (similar to the various tool shapes of loading machines as loaders, excavators, bulldozers) are presented in the case of plane strain conditions. On the basis of the mathematical theory of plasticity, theoretical solutions are obtained assuming the associated flow rule and the Coulomb-Mohr limit state, regarding incipient plastic motion. The analysis of several boundary problems shows that using only three types of simple kinematically admissible mechanisms it is possible to obtain results close to complete solutions or statically admissible solutions (obtained using the method of characteristics) for both the pushing force estimation and the motion area range.